Chinese undergraduates’ English reading self-efficacy, intrinsic cognitive load, boredom, and performance: A moderated mediation model - Jiang, Chenjuan (Frontiers in Psychology, 2023)
Research findings from various academic domains have demonstrated that students’ self-efficacy influences their academic performance while limited studies have explored how foreign language reading self-efficacy influences reading performance. The purpose of this quantitative study was to explore the relationship between reading self-efficacy, cognitive load, boredom and reading performance. The participants were 272 EFL learners at a comprehensive university in China, who took a compulsory English course for improving their English reading and writing proficiency. Data were analyzed through SPSS and structural equation modelling. The result of the study provided support for the hypothesized relationships. Student’s English reading self-efficacy is positively related to their reading performance and negatively related to reading cognitive load. Their intrinsic cognitive load during the reading comprehension is negatively related to reading performance. The reading boredom is negatively related to reading self-efficacy and reading performance but positively related to cognitive load. Furthermore, students’ cognitive load mediates the relationship between reading self-efficacy and performance while the negative achievement emotion boredom moderates the relationship between reading self-efficacy and cognitive load. The research highlights the importance of cognitive and emotional factors in influencing the relationship between foreign language reading self-efficacy and reading performance. Implications for EFL teachers and researchers are discussed.